Stenoptilia stigmatodactyla - Ustjuzhanina, Anna (Zenodo, 2017)
StenoPtilia stigmatodactyla (Zeller, 1852) Material examined . 1 ♀ (CUK), Tere-Khol', 15.vii.2000, O. Kosterin. Distribution. Europe, Transcaucasia, Iran, Kazakhstan, South Siberia, Yakutia, Magadan region. Published as part of Ustjuzhanina, Anna, 2017, Pterophoridae (Lepidoptera) fauna of the Republic of Tuva, pp. 317-328 in Zootaxa 4319 (2) on page 322, DOI:10.11646/zootaxa.4319.2.3, http://zenodo.org/record/889135